Prognostic and Theranostic Biomarkers in Ovarian Clear Cell Carcinoma. (March 2022) - Wiedemeyer, Katharina; Wang, Linyuan; Kang, Eun Young; Liu, Shuhong; Ou, Young; Kelemen, Linda E.; Feil, Lukas; Anglesio, Michael S.; Glaze, Sarah; Ghatage, Prafull; Nelson, Gregg S.; Köbel, Martin
Abstract : In this study, we aimed to test whether prognostic biomarkers can achieve a clinically relevant stratification of patients with stage I ovarian clear cell carcinoma (OCCC) and to survey the expression of 10 selected actionable targets (theranostic biomarkers) in stage II to IV cases. From the population-based Alberta Ovarian Tumor Type study, 160 samples of OCCC were evaluated by immunohistochemistry and/or silver-enhanced in situ hybridization for the status of 5 prognostic (p53, p16, IGF2BP3, CCNE1, FOLR1) and 10 theranostic biomarkers (ALK, BRAF V600E, ERBB2, ER, MET, MMR, PR, ROS1, NTRK1-3, VEGFR2). Kaplan-Meier survival analyses were performed. Cases with abnormal p53 or combined p16/IFG2BP3 abnormal expression identified a small subset of patients (6/54 cases) with stage I OCCC with an aggressive course (5-yr ovarian cancer-specific survival of 33.3%, compared with 91.5% in the other stage I cases). Among theranostic targets, ERBB2 amplification was present in 11/158 (7%) of OCCC, while MET was ubiquitously expressed in OCCC similar to a variety of normal control tissues. ER/PR showed a low prevalence of expression. No abnormal expression was detected for any of the other targets. We propose a combination of 3 biomarkers (p53, p16, IGF2BP3) to predict prognosis and the potential need for adjuvant therapy for patients with stage I OCCC. This finding requires replication in larger cohorts. In addition, OCCC could be tested for ERBB2 amplification for inclusion in gynecological basket trials targeting this alteration.